Young sociologists in the mirror: digital ethnographies of young people online - Crescenzo, Nadia (Frontiers in Sociology, 2023)
The aim of the paper is to analyze how the qualitative method represents a tool capable of analyzing the youth experience in the digital context. The contribution takes as a starting point the results of a didactic exercise experimented in the course of “Sociology of youth cultures” by the students of the University of Salerno in which the qualitative method of netnography was applied to study some youth practices online. During the work carried out, the qualitative method represented a way to study the universe of young people, entering the “new digital habitats,” where young people create and reproduce relationships, identities and spaces for socializing. The results showed, first of all, how the method of netnography made it possible to analyze the contours and transformations of youth practices in digital spaces, and secondly it allowed to arouse “reflexivity” in young people, it allowed to activate a process in which young people have looked at themselves “in the mirror,” entering the folds of the virtual worlds of youth and are amazed at the way in which they represent themselves, becoming observers and observers of that same reality. The qualitative approach has therefore allowed the students to grasp the youth practices in which they are immersed in their daily life from another point of view and have had the opportunity to analyze them from the inside and develop a high degree of reflexivity that it helped to reach a different awareness of being young today and of being able to read the cultural dynamics of youth with a critical eye.